2022
DOI: 10.1371/journal.pone.0262221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of using complementary and alternative medicine for the treatment of chronic illnesses: A multicenter study in Bangladesh

Abstract: Background While conventional medicine (CM) is commonly used to treat non-communicable diseases (NCDs), complementary and alternative medicine (CAM) is gaining popularity as a healthcare option in Bangladesh. We aimed to investigate the prevalence and factors associated with using CAM solely and using CAM in conjunction with CM for chronic illness treatment among NCD patients in Bangladesh. Methods A multicenter cross-sectional study was conducted, including 549 adults with a confirmed chronic illness diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 23 publications
6
30
2
Order By: Relevance
“…In Saudi Arabia, it is still too early to assess how open doctors are to discussing CAM and how ready they are to answer patients’ questions about it. The CAM disclosure rate in this study is relatively better than what has been reported previously [ 11 ]. Many of the participants believe that it is not important for doctors to know about their CAM use and they have little knowledge about CAM.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In Saudi Arabia, it is still too early to assess how open doctors are to discussing CAM and how ready they are to answer patients’ questions about it. The CAM disclosure rate in this study is relatively better than what has been reported previously [ 11 ]. Many of the participants believe that it is not important for doctors to know about their CAM use and they have little knowledge about CAM.…”
Section: Discussioncontrasting
confidence: 62%
“…As reported previously, the study participants frequently received suggestions and advice concerning CAM from their friends and relatives [ 11 , 13 ]. Despite the fact that medical professionals should be the best source of information on CAM, only a few reported consulting them for advice or conducting their own search [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the National Center for Complementary and Integrative Health affiliated to the National Institute of Health (NIH), CAMs fall into the practice of "integrative health" which brings conventional and complementary approaches together in a coordinated way. The use of CAMs has increased in recent times to manage and treat various chronic disorders, such as diabetes and cancer [1][2][3][4][5][6][7][8][9]. Recently, 170 of the 194 member states of the World Health Organization recognized and acknowledged the use of complementary medicines.…”
Section: Introductionmentioning
confidence: 99%
“…While conventional medicine has made significant progress in Bangladesh, a considerable number of people uses various forms of CAM treatment for their primary health care [12][13][14]. According to a recent survey, 32.8% of patients with chronic disease used some form of CAM for their chronic disease management in Bangladesh [15]. Another recent study from Bangladesh reported that 33% of diabetic patients in the northern part of the country used some different types of CAM to manage or treat their condition [16].…”
Section: Introductionmentioning
confidence: 99%